Kemampuan Analisis Peserta Didik Terhadap Materi Pencemaran Lingkungan Melalui Lembar Kerja Inovatif - Yula Miranda; Agus Sadono; Nuriman Wijaya; Gress Melinda Pangaribuan; Erlina Kalawa; Gugun Nurwaid; Marete Marete (FKIP Universitas Palangka Raya, 2021)
The problem of this research showed that there was a gap between the goal of Basic Competencies (KD) and the achieved indicators. The research goal produced a Problem-Based Students Worksheet that could improve analytical skills on environmental pollution material, such as the skills in element analysis, relationship analysis, and principle organizing analysis using operational verbs to “analyze, detect, diagnose, test, solve, correlate, diagram, conclude, discover, and train”. The research method with the ADDIE development model included analysis, design, development, implementation, and evaluation. The abilities produced in the student worksheets in this study included high-level thinking that was adapted to basic competencies on environmental pollution material in the school curriculum, analytical skills and identification abilities, and correlated a pollution concept. Research produced LKPD products as a result of development and outputs produced by scientific works in the category of scientific articles published in accredited national journals and copyright IPR. The results of the study could enable students to analyze problems in environmental pollution material and LKPD contributed very well as a medium, a source of learning for students. Problem-based student worksheets could improve students' ability to analyze problems in the X-MIPA class with an N-Gain 0.86 in the high category, while in the X-IIS Specialization class there was an increase in analytical skills with an N-Gain 0.42 in the medium category.